Mokken Scale Analysis of Lifetime Responses on the Columbia Suicide Severity Rating Scale's Severity of Ideation Subscale. (September 2021) - Tabares, Jeffrey V.; Butner, Jonathan E.; Bryan, Craig J.; A. Harris, Julia
Suicide risk screening assumes that suicidal thoughts and behaviors exist on a continuous, hierarchical spectrum with some suicidal thoughts implicated with greater risk for suicidal behaviors. However, screening measures based on the hierarchical model may not capture the suicide risk construct. This study assessed psychometric properties of the Columbia Suicide Severity Rating Scale (CSSRS) for (a) between- and within-person measurement dimensions, (b) item utility in capturing the suicide risk construct, and (c) tenability of a hierarchical risk model. We found that the CSSRS functions differentially between and within individuals, CSSRS items capture more suicide risk construct, and that CSSRS items in current practice likely appear in the correct order. The current CSSRS reasonably represents within-person suicide risk, but not between-person risk. Scale norms or alternate scoring could facilitate functional equivalence and utility for between- and within-person CSSRS dimensions.